Manajemen Risiko Dalam Proyek Pembangunan: Tantangan, Strategi Mitigasi, Dan Perspektif Internasional - Nisa istiqomah HRP; Tania Ayundasyfa; Boni Saputra (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
Risk management is a critical element in the governance of development projects, particularly within the framework of public governance that emphasizes accountability, transparency, and the efficient use of resources. This article aims to examine the theoretical foundations of risk management, identify the key challenges in its implementation, and formulate effective mitigation strategies in the context of development projects. A qualitative approach with a descriptive-analytical literature review method was employed, drawing on international journals, reports from global institutions such as the World Bank, IPCC, and UNDRR, as well as policy documents from both developing and developed countries. The findings indicate that risks in development projects can be categorized into seven main groups: technical, financial, regulatory, environmental, socio-political, institutional, and informational risks. The most significant challenges identified include project environment complexity, information asymmetry, limited institutional capacity, corruption, and escalating climate-related risks. Effective mitigation strategies encompass the application of an integrated risk management framework based on ISO 31000:2018, institutional capacity building, enhancement of transparency and accountability, collaborative governance approaches, and the utilization of technologies such as AI, GIS, BIM, and blockchain. This study concludes that the effectiveness of risk management is fundamentally determined by governance quality and must be integrated with institutional reform agendas and the principles of sustainable development.